The value of peripatetic economists: a sesqui-difference evaluation of Bob Gregory - Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2005)
I ask generally whether a country can benefit from the temporary importation of human capital, and specifically whether a program that attracts large groups of academic visitors to a distant country benefits it by generating additional scholarly research on local issues. Using the list of visitors to the ANU Research School's Economics Program, I estimate this impact from responses to a survey in which visitors described their research before and after their visit and designated as a control person another economist who had a similar career but had not visited. The matching of the control may be viewed as being along both observable and (to the researcher) unobservable characteristics of the treated and control individuals. The results show a highly significant ceteris paribus impact of such visits on the visitor's subsequent research. Valuing this extra research based on the scholarly citations it received and the effects of citations on salaries shows a substantial monetary impact of visiting economists. Less tangible additional impacts in terms of research style also clearly result.
Keywords: A14; C21; J24; 330; evaluation; control groups; bibliometrics; human capital; Wirtschaftswissenschaftler; Erwerbsverlauf; Humankapital; Schätzung; Australien; Auslandsaufenthalt